THE INFLUENCE OF OPERATING INCOME AND OPERATING COSTS ON NET PROFIT AT PT GUDANG GARAM INDONESIA TBK. - Ananda, Febryandhie; Fajriansyah, Fajriansyah (Yayasan Education and Social Center, 2025)
This study aims to examine the effect of operating income and operating costs on net profit at PT Gudang Garam Indonesia Tbk. The type of research used is quantitative research, with data obtained from literature studies in relevant journals and books. The sample in this study consists of 32 quarterly financial reports from the period 2016 to 2023. The data analysis techniques employed include descriptive statistical tests, classical assumption tests, multiple linear regression analysis, multiple correlation coefficients, adjusted R-squared tests, and t-tests. This research was conducted to test the proposed hypotheses regarding the influence of independent variables on the dependent variable. The findings of the study reveal that operating income has a negative and significant effect on net profit, indicating that an increase in operating income does not necessarily lead to a higher net profit. Conversely, operating costs have a positive and significant effect on net profit, suggesting that efficient management of operating expenses can positively contribute to the company’s net profit. These results provide insights into the financial dynamics of PT Gudang Garam Tbk.